(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
Sustainable food production has become a global priority due to the increasing demand for food, population growth, and environmental degradation. Modern agricultural and food production systems face significant challenges, including climate change, water scarcity, soil degradation, biodiversity loss, and greenhouse gas emissions. Sustainable food production aims to meet current food needs while preserving natural resources and ensuring environmental protection for future generations. This article examines the relationship between sustainable food production and environmental challenges, highlighting innovative approaches and technologies that promote ecological balance and resource efficiency. The study emphasizes the importance of sustainable agricultural practices, waste reduction, renewable energy utilization, and environmentally friendly food processing technologies. The findings demonstrate that sustainable food production plays a crucial role in achieving food security, environmental conservation, and long-term economic development.